Effective input order of dynamics learning tree. (1st February 2018) - Kim, Chyon Hae; Hama, Shohei; Hirai, Ryo; Takahashi, Kuniyuki; Yamada, Hiroki; Ogata, Tetsuya; Sugano, Shigeki
Abstract: In this paper, we discuss about the learning performance of dynamics learning tree (DLT) while mainly focusing on the implementation on robot arms. We propose an input-order-designing method for DLT. DLT has been applied to the modeling of boat, vehicle, and humanoid robot. However, the relationship between the input order and the performance of DLT has not been investigated. In the proposed method, a developer is able to design an effective input order intuitively. The proposed method was validated in the model learning tasks on a simulated robot manipulator, a real robot manipulator, and a simulated vehicle. The first/second manipulator was equipped with flexible arm/finger joints that made uncertainty around the trajectories of manipulated objects. In all of the cases, the proposed method improved the performance of DLT. Abstract :